2022
DOI: 10.1002/mds.28999
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Noradrenergic Activity to Anxiety‐Induced Freezing of Gait

Abstract: Background Freezing of gait is a complex paroxysmal phenomenon that is associated with a variety of sensorimotor, cognitive and affective deficits, and significantly impacts quality of life in patients with Parkinson's disease (PD). Despite a growing body of evidence that suggests anxiety may be a crucial contributor to freezing of gait, no research study to date has investigated neural underpinnings of anxiety‐induced freezing of gait. Objective Here, we aimed to investigate how anxiety‐inducing contexts migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
(187 reference statements)
0
14
0
Order By: Relevance
“…Overactivation of the locus coeruleus (i.e., supraoptimal arousal), on the other hand, may lead to a situation that allows for an element of increased, dysfunctional ‘cross-talk’ between competing inputs of these complementary networks [ 51 ]. In PD specifically, this has been associated with detrimental effects on motor function, particularly the occurrence of anxiety-induced freezing of gait [ 52 54 ]. Unfortunately, the ability to adaptively employ the locus coeruleus to optimally modulate the interaction of compensatory networks may be affected by the profound degeneration of the nucleus in PD, and this is compounded by dysfunction of cortical regions in charge of regulating arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of the locus coeruleus (i.e., supraoptimal arousal), on the other hand, may lead to a situation that allows for an element of increased, dysfunctional ‘cross-talk’ between competing inputs of these complementary networks [ 51 ]. In PD specifically, this has been associated with detrimental effects on motor function, particularly the occurrence of anxiety-induced freezing of gait [ 52 54 ]. Unfortunately, the ability to adaptively employ the locus coeruleus to optimally modulate the interaction of compensatory networks may be affected by the profound degeneration of the nucleus in PD, and this is compounded by dysfunction of cortical regions in charge of regulating arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have disclosed that anxiety and depression are common non-motor features in PD-FOG that crucially contribute to FOG occurrence (61). It is suggested that emotional loading could detract attentional resources in PD-FOG, in turn leading to abrupt gait dysfunction (4,62). Thus, to reduce the potential confounding effects of emotion, we added the HAMA and HAMD-24 scores as covariates in imaging analyses.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly apparent that the neuropathological changes of PD extend well beyond the nigrostriatal system, pointing especially to the early involvement of the LC in the neurodegenerative process underlying the disease [ 72 , 73 ]. Of interest, the NA system is thought to be involved in the pathophysiology of gait disorders in PD, such as freezing of gait which can be viewed as a failure to initiate movement [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%